2017
DOI: 10.1186/s12916-017-0885-6
|View full text |Cite
|
Sign up to set email alerts
|

Pre-diagnostic metabolite concentrations and prostate cancer risk in 1077 cases and 1077 matched controls in the European Prospective Investigation into Cancer and Nutrition

Abstract: BackgroundLittle is known about how pre-diagnostic metabolites in blood relate to risk of prostate cancer. We aimed to investigate the prospective association between plasma metabolite concentrations and risk of prostate cancer overall, and by time to diagnosis and tumour characteristics, and risk of death from prostate cancer.MethodsIn a case-control study nested in the European Prospective Investigation into Cancer and Nutrition, pre-diagnostic plasma concentrations of 122 metabolites (including acylcarnitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
82
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 53 publications
(102 citation statements)
references
References 45 publications
12
82
5
Order By: Relevance
“…In line with our results, analyses in ATBC showed an inverse association between metabolites related to energy metabolism (α‐ketoglutarate and citrate) and risk of aggressive prostate cancer . Our previous study in EPIC also suggested inverse associations of acylcarnitines and taurine with advanced prostate cancer . There are also some published data on dietary and lifestyle correlates of the metabolites in treelet component 2 …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In line with our results, analyses in ATBC showed an inverse association between metabolites related to energy metabolism (α‐ketoglutarate and citrate) and risk of aggressive prostate cancer . Our previous study in EPIC also suggested inverse associations of acylcarnitines and taurine with advanced prostate cancer . There are also some published data on dietary and lifestyle correlates of the metabolites in treelet component 2 …”
Section: Discussionsupporting
confidence: 91%
“…The current results on phosphatidylcholines and sphingomyelins (treelet component 1) and risk are broadly consistent with those of other prospective studies investigating individual metabolites, including our previously published results, which were conducted in a subset (~35%) of the current study population. For example, we previously reported inverse associations of many individual phosphatidylcholines, all of which were included with positive loadings in treelet component 1 or 3, with risk of advanced stage prostate cancer, and some associations remained when restricting the analysis to aggressive prostate cancer.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations